Restricted teashirt expression confers eye-specific responsiveness to Dpp and Wg signals during eye specification in Drosophila. - Bessa, J.; Casares, F. (Development, 2005)
In Drosophila, the eye primordium is specified as a subdomain of the larval eye disc. Here, we show that the Zn-finger transcription factor teashirt (tsh) marks the region of the early eye disc where the eye primordium will form. Moreover, tsh misexpression directs eye primordium formation in disc regions normally destined to form head capsule, something the eye selector genes eyeless (ey) and twin of eyeless (toy) are unable to do on their own. We present evidence that tsh induces eye specification, at least in part, by allowing the activation of eye specification genes by the wingless (wg) and decapentaplegic (dpp) signaling pathways. Under these conditions, though, terminal eye differentiation proceeds only if tsh expression is transient.